If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5m + 7 + -42 = 0 Reorder the terms: 7 + -42 + 5m = 0 Combine like terms: 7 + -42 = -35 -35 + 5m = 0 Solving -35 + 5m = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '35' to each side of the equation. -35 + 35 + 5m = 0 + 35 Combine like terms: -35 + 35 = 0 0 + 5m = 0 + 35 5m = 0 + 35 Combine like terms: 0 + 35 = 35 5m = 35 Divide each side by '5'. m = 7 Simplifying m = 7
| 5u^2-18u=-9 | | 6n-6=2n+20 | | 4-3x=9+x-5x | | .75=0.4p+100 | | 0.25+y=225 | | 1.66x-9=61x-201 | | 3m=2(4+x)salveforx | | 5x-3*5=15 | | 9x-40=7x-37 | | (x+14)+3x=180 | | 19-3n=13 | | -37+6x=19+2x | | 3p+5q=7 | | 6+5g=3g+20 | | 4x-10=7x-9 | | 10=0.83(n+6) | | 2-(-2)s=6 | | -x-18=36 | | 0.5x+.01x+12+1x-5=9.96 | | 3d+4(-3)=11 | | 2661=63+63(n-1) | | x^2-kx+9=y | | 4x+3a=bx+2.5a-5 | | 5(x+3)-2=2x+9 | | 6x+8x-42=84-7x | | v-7.5=3.4 | | x^2+9x=15 | | 3r+1=r+8 | | 5r+7=-13+7r | | 9d+4(-7)=15 | | -7+4(1-5x)=x+39 | | y+6.4=9.66 |